Chronic unremitting headache associated with Lyme disease-like illness - Pedro Andre Kowacs; Rodrigo Tomazini Martins; Elcio Juliato Piovesan; Maria Cristina Araujo Pinto; Natalino Hagime Yoshinari (Arquivos de Neuro-Psiquiatria)
The Brazilian Lyme-disease-like illness (BLDLI) or Baggio-Yoshinari syndrome is a unique zoonosis found in Brazil. It reproduces all the clinical symptoms of Lyme disease except for the high frequencies of relapse and the presence of autoimmune manifestations. Two cases of borreliosis manifesting with unremitting headache, which is a symptom associated with late-stage BLDLI, were presented. Clinical, therapeutic, and prognostic aspects of the BLDLI and its associated headaches were showed and discussed in this article. BLDLI diagnosis requires additional attention by physicians, since the disease has a tendency to progress to the late, recurrent stage or the chronic form, and the associated headache can be confused with chronic primary headache or with analgesic-overuse one. Special attention should be paid to patients with headaches who have traveled to endemic areas.